Visualizing animation databases - Akanksha (Animo Repository, 2003)
We consider a repository of animation models and motions that can be reused to generate new animation sequences. For instance, a user can retrieve an animation of a dog kicking its leg (in air) and manipulate the result to generate a new animation where the dog is kicking a ball. In this particular example, inverse kinematics technique can be used to retarget the kicking motion of a dog to a ball. This approach of reusing models and motions to generate new animation sequences can be facilitated by operations such as querying of animation databases for required models and motions, and manipulation of the query results to meet new constraints. However, manipulation operations such as motion retargeting are quite complex in nature. Hence, there is a need for visualizing the queries on animation databases as well as the manipulation operations on the query results. In this paper, we propose a visually interactive method for reusing motions and models, by adjusting the query results from animation databases for new situations while at the same time, keeping the desired properties of the original models and motions. Here, a user first queries for animation objects, i.e., geometric models and motions. Then, the user interactively makes new animations by visually manipulating the query results. Depending on the orders in which the GUIs (Graphical User Interfaces) are invoked and the parameters are changed, the system automatically generates a sequence of operations, a list of SQL-like syntax commands, and applies it to the query results of motions and models. With the help of visualization tools, the user can view the changes before accepting them.